Icaritin and lenvatinib treatment for unresectable localized progressive pancreatic cancer: a report of six cases - Xiaolong Liu; Jianguo Lu; Xinyu Dong; Yizhuo Zhang; Guixing Jiang; Yanlong Cao; Defei Hong (Annals of Medicine)
Background Pancreatic cancer is very difficult to detect in its early stages, and its rapid progression and poor prognosis make it a significant therapeutic challenge. Existing treatment modalities, whether standalone or combined, offer limited efficacy, highlighting an urgent need for more effective and less toxic therapeutic strategies.Patients We analyze six cases of pancreatic cancer, each undergoing a novel treatment regimen integrating chemotherapy, targeted therapy, immune therapy, and icaritin.Results The outcomes demonstrate varying degrees of improvement in all cases. Partial responses were observed in cases 1 and 3, with some tumor shrinkage. Cases 4 and 5 showed limited relief following a slight decrease in tumor size. In cases 2 and 6, no significant progression of the lesion was observed. These results highlight the potential efficacy of this multifaceted approach.Conclusion Integrating icaritin with chemotherapy, immunotherapy, and/or targeted therapies shows potential as an exploratory approach in managing advanced, locally progressive, or metastatic pancreatic cancer, though further validation is required.